School Psychology and Cultural Competence: Room to Grow?. Issue 7 (November 2019) - Johnson, Jill L.; Bahr, Michael W.; Navarro, Virginia L.
This study investigated how the concept of cultural competence was represented in three 2010 policy documents on service delivery, ethics, and credentialing by the National Association of School Psychologists. Qualitative analysis identified substantial sections of discourse focusing on cultural competence and, to a lesser extent, social justice, but neither concept was clearly defined with examples from everyday practice. From a policy perspective, a stronger focus on the centrality of cultural competence in school psychology training and practice is needed to improve outcomes for increasingly diverse children and families. Implications for policy development, professional development, and future research are discussed.